Studi Eksperimental Nilai Kekerasan Semikonduktor ZnO terhadap Variasi Beban Kompaksi - Agus Kurniawan; Bayu Prabandono; Sularman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
One important process in manufacturing pellet material is a compaction. This research will study the hardness value at ZnO semiconductor material that is compacted with different pressure. The first material is pure ZnO that was grinded with agate mortar, filtered and compacted with pressure are 10 bar, 20 bar and 30 bar so the pellet form were shaped. The size of pellet is Æ 13 x 2 mm. Furthermore, these pellet sintered at temperature 1300oC than it will test by vikers microhardness testing. The testing result is that the greatest vikers microhardness at the material that is compact at 30 bar. The mean value of it is 213.85 Hv. The greater of compacting pressure given the higher value of the material's hardness. Nevertheless, the magnitude of compacting pressure must consider the ability of the compacting mold.